Diatesis dalam Kicauan Twitter Anak Usia Remaja - Nicky Rosadi (LITERATUS, 2019)
The purpose of this research was to know diathesis contained in Twitter tweets of teenagers. Research conducted in Jakarta, during the even semester of the 2014/2015 academic year used a qualitative descriptive analysis method with content analysis. The object of this research is Twitter text written by teenagers. The instrument used in this study was the researcher himself who was assisted by the data analysis table. Based on the results of the analysis, it can be seen that the most common diathesis is active diathesis with the appearance of 40% of the total data available. Second is a causative diathesis with the occurrence of 21.54% of the total data. From the two biggest occurrences, it is seen that diathesis that refers to active actions/actions is the most widely used. So, it can be concluded that Twitter tweets of teenagers are more dominant using active diathesis